Swift heavy ion irradiation induced modification of the microstructure of NiO thin films - Mallick P.; Rath C.; Prakash J.; Mishra D.K.; Choudhary R.J.; Phase D.M.; Tripathi A.; Avasthi D.K.; Kanjilal D.; Mishra N.C. (My University, 2025)
NiO nanoparticle films (200 nm thick) grown on Si substrates by pulsed laser deposition method were irradiated by 200 MeV Ag15+ ions. The films were characterized by glancing angle X-ray diffraction, atomic force microscopy and optical absorption spectroscopy. Though electronic energy loss of 200 MeV Ag ions in NiO matrix was higher than the threshold electronic energy loss for creation of columnar defects, films remained crystalline with the initial fcc structure even up to a fluence of 5 × 1013 ions cm-2, where ion tracks are expected to overlap. Irradiation however modified the microstructure of the NiO films considerably. The grain size decreased with increasing ion fluence, which led to reduced surface roughness and increased optical band gap due to quantum confinement. These results correlate well with variation of the power spectral density exponent with ion fluence, which indicate that at high ion fluences, the evolution of surface morphology is governed by surface diffusion. © 2010 Elsevier B.V. All rights reserved.